RECONSIDERING DINAR GOLD MONEY AS INTERNATIONAL TRADE CURRENCY: LITERATURE STUDY - Andri Soemitra; Rifki Ismal; Sanusi Gazali Pane; Bambang Lesmono; Ridha Alhamdi; Muhammad Zulkifli Hasibuan (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
It is common knowledge that the economic crisis is caused by the failure of paper money to maintain price stability, devaluation, and redistribution effects. Exchange rate fluctuations severely hamper international trade and finance. On the other hand, gold has a more stable exchange rate and is relatively exchangeable for various needs. Gold has the same intrinsic value as any other commodity. However, it can serve as an international unit or units of account. The funds can be used as settlements in international trade payments. In the context of the optimum currency area (OCA), trade barriers between countries are increasingly being removed, including forming a common currency. The use of gold as a form of union currency would facilitate payments and benefit member states. International payment arrangements can also be made within the framework of bilateral and multilateral payment agreements. We support the analytical model of Ahmed Kamel Mydin Meera which reveals that the gold dinar can replace the fiat money as a payment transaction, as well as as a settlement in international trade with a note after economic and monetary integration is formed.